Coherent optical and RF receiver for simultaneously transferring frequencies in optical and RF domain - Feng, Zitong; Zhang, Xi; Wu, Rui; Yang, Fei; Gui, Youzhen; Cai, Haiwen; Wang, Dongjin (Joint Conference of the IEEE International Frequency Control and the European Frequency and Time Forum, 2019)
A simple and novel coherent optical frequency and radio frequency (RF) receiver (CORR) for simultaneously distribution of optical and RF application is presented. This technology is based on an electro-absorption modulator (EAM) integrated with a distributed feedback (DFB) laser subject to optical injection. Experiments show that the amplitude modulation (AM) side lobes of the RF signal in the optical carrier were completely suppressed after injection-locking, and the RF signal can recover from the EAM at the same time. Moreover, the stability of optical and RF signal output from the CORR will not be deteriorated. Recovered optical and RF signal reached a frequency stability of 10 -20 and 10 -16 for 1000 s averaging period, respectively.